Study on clinical profile of hyponatremia in patients admitted to the MIMS in Northern Andhra Pradesh, India - Sastry, Anand Sankar; Praneetha, Buridi (International Journal of Research in Medical Sciences, 2019)
Background: Hyponatremia, most common electrolyte disorder has symptomatology ranging from asymptomatic to being comatose and etiologically from simple G.I. loss to chronic illnesses like CCF, CKD. Very sparse study has been done in this region on clinic-epidemiological profile of hyponatremia. The aims and objective of this study was to find out most common etiology, type, clinical features and outcome in hospitalised hyponatremic patients and to Correlate clinical profile and outcome with etiology, severity and treatment. Methods: The present observational study was conducted in department of medicine, Maharajah’s Institute of medical sciences, for two months. All patients aged ≥15 years having true hyponatremia were included. Detailed history, examination, relevant investigations including serum and urinary Na were done. Patients were classified to euvolemic, hypervolemic and hypovolemic depending on volume status and proper etiologies were determined in each group. Results: Of 50 patients included, mean age was 50.12±8.8 years. Hyponatremia was more common in older age group>40 years (P<0.05%). CNS manifestations were more prevalent in patients with Na<125 Meq. (80%) P< 0.05%. Hypervolemic was most common type (50%) followed by hypovolemic (34%) and euvolemic (16%). CKD was the most common cause overall (24%) and also among hypervolemic type (40%). Conclusions: Hyponatremia was more predominant in elderly age group (P<0.05%). It is more in 40-60 years age group. Hypervolemic type (50%) of hyponatremia is most common type of the hyponatremia and CKD (24%), to be most common cause of the hyponatremia attributed to Uddanam nephropathy in this region.